Comparison of glycemic control after pancreas transplantation for Type 1 and Type 2 diabetic recipients at a high volume center. Issue 8 (15th July 2019) - Andacoglu, Oya M.; Himmler, Amber; Geng, Xue; Ahn, Jaeil; Ghasemian, Seyed; Cooper, Matthew; Abrams, Peter
Abstract: Introduction: The number of pancreas transplants (PTX) in patients with Type 2 diabetes (T2DM) has increased in response to excellent outcomes in appropriately selected patients. Not all pancreas transplant centers share an enthusiasm for performing PTX for T2DM out of concern for increased complication rates. This study aims to clarify the characteristics of T2DM recipients with successful outcomes to clarify which candidates are more suitable for PTX as means of maximizing access to this highly effective therapy for Type 2 patients. Methods & Results: At MedStar Georgetown Transplant Institute, 50 patients underwent pancreas transplant between 2013 and 2016. Based on patient characteristics, 38 (78%) were categorized as T1DM, and 11 (22%) were considered T2DM. One case was excluded due to early graft loss. The estimated age of diabetes onset was significantly different between T1DM and T2DM cohorts (13 years vs. 29 years, P < .001). T2DM patients had significantly higher preoperative C‐peptide levels (4.11 vs. 0.05, P < .001). Preoperative HbA1c, preoperative Body Mass Index (BMI), number of diabetic complications, and hemodialysis status were similar between both groups. At 2‐year follow‐up, there was no statistical difference in glycemic control between the two groups (T1DM vs. T2DM). Infectious complications and readmission rates were similar. Other trends that did not meet statistical significance included T1DM group with a slightly higher mortality and re‐intervention rate. The T2DM group demonstrated higher BMI, higher rejection rates, and higher short‐term postoperative insulin requirements. Graft survival was 95% and 82% for T1 and T2DM at 2 years post‐transplant, respectively. Conclusion: Successful PTX in T1DM and T2DM recipient groups resulted in comparable glycemic control at 2‐year post‐transplant follow‐up. T2DM group had a trend toward higher BMI as well as higher rates of rejection, temporary insulin requirement and graft failure, although none of these trends reached statistical significance. These results suggest that strict classification of T1 and T2DM by itself may not be relevant to achieving excellent outcomes in pancreas transplantation and, therefore, patient selection for PTX should not be based primarily on this classification.